Latitudinal patterns in tachinid parasitoid diversity (Diptera: Tachinidae): a review of the evidence. Issue 5 (6th April 2020) - Burington, Zelia L.; Inclán‐Luna, Diego Javier; Pollet, Marc; Stireman, John O.
Abstract: Insect parasitoids may be an exception to the typical biogeographic pattern of increasing species richness at lower latitudes exhibited by most taxa. Evidence for this 'anomalous' latitudinal gradient has been derived from observations of hymenopteran parasitoids and it has been argued that other parasitoid groups should show a similar pattern of diversity. Several mechanisms have been proposed to explain this disparity, most notably the nasty host and resource fragmentation hypotheses. We review and evaluate these hypotheses with respect to tachinid flies (Diptera: Tachinidae), and bring to the argument evidence from eight trapping surveys from temperate and tropical regions in the Americas including the United States, Costa Rica, and Ecuador. We find no evidence that tachinid fly diversity is lower in the tropics than in the temperate region. Our results, along with other lines of evidence, rather suggest that New World Tachinidae likely conform to the same negative relationship between latitude and richness as their largely phytophagous host taxa. We discuss geographic patterns of tachinid diversity in relation to ecological and evolutionary processes, and why they may differ from their hymenopteran parasitoid counterparts. Parasitoid taxa appear to vary strongly in their diversity responses to latitude and we concur with previous researchers that more survey data are necessary to reach strong conclusions about parasitoid latitudinal diversity patterns. Abstract : Some hymenopteran parasitoid taxa appear to be more diverse at temperate latitudes than near the equator; however, such patterns have not been examined for tachinid parasitoids. We review evidence and arguments concerning latitudinal gradients in parasitoid diversity and provide evidence that tachinids are likely more diverse in the tropics based on surveys in the Americas. We discuss geographic patterns of tachinid diversity, why they may differ from their hymenopteran parasitoid counterparts, and the problems faced in inferring diversity patterns for parasitoids.